Pengaruh Financial Self Efficacy dan Financial Knowledge Terhadap Pengelolaan Keuangan Pribadi Mahasiswa S-1 Akuntansi - Novyarni, Nelli; Atikah, Destria Ayu; Harni, Reni; Krisnando (Jurnal EMT KITA, 2024)
Personal financial management is something that is important for all groups, one of which is students. Students are always identified with an up-to-date attitude to meet primary and secondary needs. This needs to be implemented to avoid failure in managing personal finances by applying Financial Knowledge. This research aims to determine the influence of financial self-efficacy and Financial Knowledge on the personal financial management of Bachelor of Accounting students. This research uses descriptive research in the form of qualitative data which is quantified using a Likert scale. The data used in this research is primary data and secondary data. The data collection technique used was through distributing questionnaires in the form of Google Forms. The data analysis method used is classical assumption testing, multiple linear regression analysis testing and hypothesis testing. The research results from data processed using SPSS Version 26 statistical calculations, found that financial self-efficacy has a significant effect on personal financial management with a significance value of 0.040 < 0.05. Financial Knowledge has a significant effect on personal financial management with a significance value of 0.007 <0.05 and simultaneously states that financial self-efficacy and Financial Knowledge simultaneously have an effect on personal financial management. Based on the research findings, it can be stated that personal financial management for Bachelor of Accounting students in fulfilling primary and secondary needs is very important